Adapting Cities to Sea Level Rise Green and Gray Strategies - Al, Stefan (Island Press/Center for Resource Economics, 2018)
"Stefan Al provides an accessible overview of typical strategies for designing an urban shoreline to respond to flooding, with a strong emphasis on past and present Dutch approaches. Numerous illustrations make it useful for non-designers, as well as students of design. I recommend the book to planners and designers who are looking for an introduction to strategies for coastal design." Kristina Hill, Associate Professor, University of California, Berkeley "Adapting Cities to Sea Level Rise is a frank typological exploration that synthesizes civil engineering, landscape, and urban design considerations into an accessible reference that highlights the adaptive and maladaptive tendencies of design. Rich with case studies, the book provides critical insights into the nuances shaping the life cycle of design interventions." Jesse M. Keenan, Faculty of Architecture, Harvard University, Graduate School of Design "With his book, Stefan Al presents an inspiring and extensive toolbox of strategies that cities can embrace to adapt to sea level rise. Al looks across the world optimistically: yes we can do it! And we must, since there is no time to waste. Adaptation is different in every place, and this book shows us how to maximize opportunities if only we work together in a truly inclusive and comprehensive way." Henk Ovink, Special Envoy for International Water Affairs, Kingdom of The Netherlands, Sherpa to the UN and World Bank High Level Panel on Water, and Principal for Rebuild by Design.